(untitled) (CIPEEX, 2022)
A MAJOR CHALLENGE IN HEALTH CARE TODAY IS ATTENTION TO THE HEALTH OF CHILDREN AND ADOLESCENTS, BECAUSE IT IS A SOCIAL GROUP THAT GOES THROUGH GREAT AND IMPORTANT PHYSIOLOGICAL AND PSYCHOLOGICAL CHANGES RELATED TO A SOCIAL INVOLVEMENT AND ITS NEW IDENTITY IN SOCIETY. THEREFORE, THE OBJECTIVE OF THIS WORK IS TO PRESENT, THROUGH A PHOTO GALLERY, THE DEVELOPMENT OF EDUCATIONAL ACTIVITIES FOR THE PROMOTION AND PREVENTION OF HEALTH RELATED TO CHILDREN OF A SOCIAL PROJECT OF THE AABB - AABB ROTARY - WELL. DYNAMIC ACTIVITIES ARE BEING DEVELOPED WITH APPROXIMATELY 150 CHILDREN IN THE AGE GROUPS 5 TO 15 YEARS OLD. THE PROPOSALS ARE DIRECTED ACCORDING TO THE AGE, THE DIVISION WAS MADE BY THE AABB INSTITUTION ITSELF, TO APPROACH AND OFFER KNOWLEDGE TO ALL, WORKING IN A PLAYFUL AND INTERACTIVE WAY. THE TOPICS COVERED ARE: CARIES AND HEALTHY EATING, DENTAL TRAUMA AND PERMANENT AND DECENT DENTITION, BULLYING AND PERSONAL HYGIENE. THE THEMES CONDUCTED HAVE SEVERAL APPROACHES THROUGH LECTURES, TALK WHEELS, GYMNASTICS, THEATER AND MUSIC. THE ACTIVITIES TAKE PLACE WEEKLY, DISTRIBUTED IN 10 DAYS. THERE IS A POSITIVE RESPONSE FROM THE TARGET AUDIENCE THAT HAS SHOWN GREAT INTEREST IN THE PROPOSED ACTIVITIES AND IN THE TOPICS ADDRESSED. EVIDENCE OF THIS POSITIVE FEEDBACK IS DEMONSTRATED IN THE MOMENTS RESERVED FOR THE CLARIFICATION OF THE DOUBTS. WE CONCLUDE THAT THE ACTIVITIES PERFORMED ALLOW AN UNDERSTANDING BY THE PUBLIC INVOLVED ABOUT THE IMPORTANCE OF ORAL AND GENERAL HEALTH CARE, GIVEN THAT IT IS A POPULATION IN AN AGE GROUP IN WHICH IT IS STILL POSSIBLE TO ESTABLISH GOOD HABITS OR EVEN CHANGES NECESSARY TO IMPROVE HEALTH CONDITIONS AND QUALITY OF LIFE. THEREFORE, THIS IS AN OPPORTUNITY TO INCREASE THE ACCESS OF CHILDREN PARTICIPATING IN A SOCIAL PROJECT TO HEALTH CARE INFORMATION. &NBSP; KEY WORDS: ADOLESCENT, CHILD, ORAL HEALTH, HEALTH PROMOTION.